Gamified Competitive Math Game for Elementary Students Using Extreme Programming: A Case Study of Math Race - Aprilliansyah, Lamda Pratama; Simatupang, Dwi Sartika (IJOEM Indonesian Journal of E-learning and Multimedia, 2025)
Background: Mathematical literacy remains a challenge for Indonesian elementary students, with low engagement linked to traditional teaching methods. Gamification and competition have shown potential to increase motivation and learning performance, while Extreme Programming (XP) offers an agile framework for educational game development.Aims: This study aims to design, develop, and evaluate Math Race: Speed Challenge, a gamified competitive math game for elementary students, integrating XP methodology to improve arithmetic skills.Methods: The research employed an applied software engineering approach using XP stages Planning, Design, Coding, and Testing. Features were defined through user needs analysis, implemented in Unity with C# and Firebase, and tested using black-box techniques. Effectiveness was measured via pretest and post-test assessments and a Likert-scale satisfaction survey.Results: All nine tested features passed functionality tests. A pretest and posttest analysis with 48 participants showed a 28.20% increase in correct answers, a 44.40% decrease in incorrect answers, and a 12.13% reduction in average answer time. A survey of 52 respondents indicated high satisfaction, especially in visual appeal and perceived learning benefits.Conclusion: The integration of gamification, competition, and XP methodology effectively enhanced students’ arithmetic performance and engagement, demonstrating the potential of agile-based game design in primary education.